HLA-DR3 antigen in the resistance to idiopathic dilated cardiomyopathy - Jin,B. (2016)
Idiopathic dilated cardiomyopathy (IDC) has been hypothesized as a multifactorial disorder initiated by an environment trigger in individuals with predisposing human leukocyte antigen (HLA) alleles. Published data on the association between HLA-DR3 antigen and IDC risk are inconclusive. To derive a more precise estimation of the relationship, a meta-analysis was performed. Studies were identified by searching the PUBMED and Embase database (starting from June 2015). A total of 19 case-control studies including 1378 cases and 10383 controls provided data on the association between HLA-DR3 antigen and genetic susceptibility to IDC. Overall, significantly decreased frequency of HLA-DR3 allele (OR=0.72; 95%CI=0.58-0.90; P=0.004) was found in patients with IDC compared with controls. When stratified by myocardial biopsy or non-biopsy cases, statistically decreased risk was found for IDC in myocardial biopsy cases (OR=0.69; 95%CI=0.57-0.84; P=0.0003). In the subgroup analysis by ethnicity, borderline statistically significantly decreased risk was found among Europeans from 12 case-control studies (OR=0.76; 95%CI=0.58-1.00; P=0.05). In conclusion, our results suggest that individuals with HLA-DR3 antigen may have a protective effect against IDC.